Prevalence of traumatic dental injuries in India: A systematic review and meta-analysis - Nitesh Tewari; Vijay Prakash Mathur; Ishrat Siddiqui; Rahul Morankar; Ankita R Verma; Ravindra Mohan Pandey (Wolters Kluwer Medknow Publications, 2020)
Objective: The aim of this systematic review and meta-analysis was to estimate the prevalence of traumatic dental injuries (TDI) in India. The secondary objective was to evaluate the prevalence rate according to the differences in gender, age, regions, type of TDI and risk factors associated with TDI. Methods: The PubMed, LILACS, Web of Science, Cochrane, CINHAL, and Scopus databases, along with the Public Health Electronic Library, TRoPHI and DoPHER were searched from 1st March to 15thApril 2019 without any restriction of language and year of publication. The qualitative synthesis was done regarding the demographics, study methods, cause of trauma, geographic location, increased overjet and inadequate lip coverage. The meta-analysis was undertaken with STATA-14 software (USA). The pooled prevalence of TDI was calculated using data extracted from 48 studies included in qualitative synthesis and meta-analysis. A sub-group meta-analysis was done by extraction of the data for age groups of 6 years and >6 years. Results: The pooled prevalence of TDI in Indian population was 13 cases in 100 individuals. The prevalence of TDI for age groups of ≤6 was 15% (males, 15%; females, 16%) and for >6 years was 12% (males, 13%; females, 8%). The most common cause of TDI was falls, and most frequent location was home. The odds ratio for occurrence of TDI and inadequate lip-coverage was 3.35 and overjet greater than 3 mm was 3.53. Conclusions: The pooled prevalence of TDI was 13% and slightly higher in children less than 6 years of age. Inadequate lip coverage and increased overjet are the risk factors associated with TDI. Heterogeneity was observed among the studies in terms of design, variables recorded, sampling, study methods and statistical methods. Majority of them also suffered from moderate to high risk of bias.